2009
DOI: 10.1097/mrr.0b013e3283298166
|View full text |Cite
|
Sign up to set email alerts
|

Sexual difficulties for persons with multiple sclerosis in New South Wales, Australia

Abstract: This 1992 study was conducted to ascertain the incidence of sexual difficulties in individuals diagnosed with multiple sclerosis (MS) living in New South Wales, Australia. New South Wales is a state lying roughly 29-36 degrees south of the equator. This is currently the largest study conducted. The anonymous questionnaire completed by 283 respondents included questions on sexual difficulties, relationship satisfaction and the ability to communicate about and seek help for the sexual difficulties. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
5
22
0
Order By: Relevance
“…In the present study, correlation analysis (Pearson and ANOVA) between demographic and clinical variables and the MSISQ-19 total scores showed a positive and significant association between sexual problems and age, which was consistent with various earlier studies [13,15,16] but in contrast to the Fraser et al study [17]. It seems that in the absence of MS, sexual problems increase with age, and that in the presence of a chronic debilitating disease like MS, the impact of age on sexual problems is exacerbated.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, correlation analysis (Pearson and ANOVA) between demographic and clinical variables and the MSISQ-19 total scores showed a positive and significant association between sexual problems and age, which was consistent with various earlier studies [13,15,16] but in contrast to the Fraser et al study [17]. It seems that in the absence of MS, sexual problems increase with age, and that in the presence of a chronic debilitating disease like MS, the impact of age on sexual problems is exacerbated.…”
Section: Discussionsupporting
confidence: 93%
“…In line with others [3,13] and in contrast with Redelman’s study [16], our results showed lower SP in patients with higher education and higher economic status. Possible explanations for this association may include a greater awareness and orientation toward sexuality matters among educated and well-off patients, as well as better access to health care and related resources.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a community-based study, men with multiple sclerosis reported masturbation difficulties, difficulty with achieving vaginal orgasms, retarded ejaculation and PE [Redelman, 2009].…”
Section: In Patients With Uti/inflammationmentioning
confidence: 99%